Analisis Implementasi Pemahaman Masyarakat Mengenai Produksi Pangan Halal Dalam Usaha-Usaha Kecil Di Daerah Medan - Wijaya, Dinda Dewi Rahma; Solin, Naia Fingkani; Febrian, Sarah; Panjaitan, Chairun Nisa; Endrico, Dede (Jurnal Manajemen Akuntansi (JUMSI), 2025)
The purpose of this study is to examine how the general public perceives halal food production in relation to the expansion of small and medium enterprises (SMEs) in the Medan region. The current halal food industry represents a new possibility to support economic development. This is claimed as a new opportunity because countries with Muslim minorities and countries with Muslim majority are both participating in the growth of the halal business. To encourage the expansion of the halal business, the Indonesian government is also trying to grow the domestic halal food and beverage sector. Explanatory research combined with quantitative is a research methodology. Communities who are consumers in the Medan area are the study population. Through initial socialization with the community and the general public, the findings of this study will help consumers of halal-certified food products in their surroundings. The general public has the right to obtain accurate information about halal-certified food products that they need as customers. The safety of Muslim food consumers, regardless of their religious beliefs or physical health, depends heavily on the information provided about the food.